Treatment of typical South African milking parlour wastewater by means of anaerobic sequencing batch reactor technology. - Du Preez, Jeanne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2010.